2020
DOI: 10.3389/fmicb.2019.03056
|View full text |Cite
|
Sign up to set email alerts
|

How to Cope With Heavy Metal Ions: Cellular and Proteome-Level Stress Response to Divalent Copper and Nickel in Halobacterium salinarum R1 Planktonic and Biofilm Cells

Abstract: Halobacterium salinarum R1 is an extremely halophilic archaeon capable of adhesion and forming biofilms, allowing it to adjust to a range of growth conditions. We have recently shown that living in biofilms facilitates its survival under Cu 2+ and Ni 2+ stress, with specific rearrangements of the biofilm architecture observed following exposition. In this study, quantitative analyses were performed by SWATH mass spectrometry to determine the respective proteomes of planktonic and biofilm cells after exposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The results demonstrated a relatively high susceptibility to zinc, and only 35% of haloarchaeal isolates could grow in the presence of 1 mM Zn 2+ . This result was in accordance with previously published [19, 33, 36, 37]. In addition, Baati et al reported that all 22 haloarchaeal strains in their study were resistant to 0.5 mM of zinc though only 22.7% were resistant to 1 mM of Zn 2+ [38].…”
Section: Discussionsupporting
confidence: 92%
“…The results demonstrated a relatively high susceptibility to zinc, and only 35% of haloarchaeal isolates could grow in the presence of 1 mM Zn 2+ . This result was in accordance with previously published [19, 33, 36, 37]. In addition, Baati et al reported that all 22 haloarchaeal strains in their study were resistant to 0.5 mM of zinc though only 22.7% were resistant to 1 mM of Zn 2+ [38].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, of the 32 non-redundant IS element-encoded proteins (Table S3) with above-average mRNA levels, only four were detected by SWATH-MS in this study, suggesting they were all post-transcriptionally repressed. By analyzing proteomics data from PeptideAtlas (76, 77) and PRIDE (78), including PXD003667 (79) and PXD015192 (80), we confirmed that 50% of the 32 transposases have been previously detected, depending on techniques and biological conditions. In addition, except for VNG_0051a, we established that these proteins bear the features required for detection by SWATH-MS. With that reasoning, we posit that the lack of detection of transposases in this study is due to their low abundance or complete absence.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, of the 33 nonredundant mobilome proteins (see Table S3 at https://doi.org/10.6084/m9.figshare.21936396.v2 ) with above-average mRNA levels, only 4 were detected by SWATH-MS in this study, suggesting that they were all post-transcriptionally repressed. By analyzing proteomics data from PeptideAtlas ( 77 , 78 ) and PRIDE ( 79 ), including data under ProteomeXchange identifiers PXD003667 ( 80 ) and PXD015192 ( 81 ), we confirmed that 50% of the 33 mobilome proteins have been previously detected, depending on the techniques and biological conditions. In addition, except for VNG_0051a, we established that these proteins bear the features required for detection by SWATH-MS. With that reasoning, we posit that the lack of detection of transposases in this study is due to their low abundance or complete absence.…”
Section: Discussionmentioning
confidence: 65%